Development of inductive sensor for determining ripeness of oil palm fruit - Harun, Noor Hasmiza (2015)
Generally, the quality of the oil palm fruit is categorized based on the texture, shape and color of the fruit. In most of the oil palm miller in the world including Malaysia, the human expert grading approach is used to inspect the maturity of the oil palm Fresh Fruit Bunch and classify them for harvesting. Human inspection is a timeconsuming method, inaccurate and often leads to mistakes where there is a high potential to grade the fruit wrongly. Therefore, an automated fruit grading system that is rapid, accurate and reliable is highly required. In the prevailing research works, none of the grading method using inductive concept is proposed and as such, an inductive based oil palm fruit sensor is proposed in this thesis, based on the resonant frequency of the air coil. The proposed structure of the inductive oil palm fruit sensor was fabricated using a non conducting material consists of an air coil as a detection part and a holder. The air coil was coiled with a copper wire of numerous diameter. The development of the inductive oil palm fruit sensor started with a ring - type shape air coil followed by a flat - type shape air coil and a dual flat-type shape air coil. The experimental testing was conducted on two types of samples namely unripe and ripe fruitlets. These samples were freshly plucked on the day of the testing. To justify the practicality of the inductive based oil palm fruit sensor, a field testing was conducted at the end of the research works. General evaluations on the resonant frequency started with the analysis of the inductance characteristics of the air coil. Then, the frequency characteristics were observed for all air coils, specifically the effects of the air coil's structure. The evaluation started with the value of the resonant frequency of the air coil was normalized. As for the inductance characteristics of the ring-type shape air coil, 24mm air coil's diameter shows the biggest difference between ripe to unripe samples. Results shows that 0.02643MHz significant difference between unripe sample to air and 0.01084MHz for ripe sample to air. As for the single flat-type air coil, the 5mm air coil's length with the 0.12mm coil diameter provides the highest percentage difference between sample and it is amongst the highest deviation value between samples. For the dual flat type air coil, the 200-140 turns configurations has improved by 371% in terms of the differences between the sample mean of both samples and 236% in terms of ratio between unripe and ripe, respectively. Finally, the field testing on three bunches of oil palm of different level of maturity displayed a growth graph of resonant frequency as the weeks passed. In sum, the inductive method of oil palm ripeness sensor offers few advantages such as passive sensor, reduced time consumption and accurate grading system. Besides, the inductive method emphasizing the resonant frequency has been proved reliable in determining the ripeness of the oil palm fruit bunches. With the advantages provided by this oil palm ripeness sensor, it is believed that inductive method would be a good alternative method to grade oil palm fruit.